Habiter un quartier RDP - Marine Suteau (EchoGéo)
This article focuses on a socio-spatial analysis of territorial change in Cape Town over time with the study of Delft South as a post-apartheid low-cost housing development program. It asks how successful or not RDP programs have been in South African cities. It argues that social differentiation is in process. In the post-apartheid, strategies to access housing and social movements are producing socio-spatial territories. Through housing and socio-spatial networks inherited from street committees, Delft South may constitute a complex peripheral space with the creation of specific racially mixed neighborhoods.